Socio-economic prerequisites for reconstruction of residential buildings of the first mass series - Osipov А. F.; Lyeka, D. R. (Ways to Improve Construction Efficiency, 2020)
The article considers normative-legal, town-planning, technical and technological aspects of the problem of deployment of mass reconstruction and modernization of large-block residential buildings of the first mass series. Analysis and generalization of practical experience in the design and implementation of mass reconstruction of residential buildings of the first mass series in Ukraine and abroad shows that with the introduction of innovative approaches to the design of spatial planning and design solutions, application of modern and well-established technologies for their reconstruction economic, resource-saving, energy-saving, environmental protection and architectural and aesthetic benefits. The analysis of modern researches testifies to expediency of introduction of methods of reconstruction. An important aspect of mass reconstruction is the economic attractiveness for investors, this parameter is most widely discussed in this article. It is also important that the moral obsolescence of the building began much earlier than the physical, and the needs of people and the requirements for comfort increased significantly, which suggests the need for mass reconstruction of buildings of the first mass series. The condition for the deployment of mass reconstruction and modernization of large residential buildings of the first mass series is a comprehensive justification of its social, urban, regulatory and technological feasibility, as well as economic attractiveness for investors. This provision is taken as the task of this article. Analysis and generalization of normative-legal, social and technological aspects of reconstruction of large-block residential buildings of the first mass series and practical experience of designing and implementation of such reconstruction are accepted as the main research methods. On the example of the city of Chernivtsi the scheme of building of the city was developed and the percentage of building by buildings of the first mass series was calculated. This allows you to pay attention to the mass nature of the issue.